INSTITUTIONAL FRAMEWORK FOR REGIONAL INTERNATIONAL SCIENTIFIC AND TECHNICAL COOPERATION IN THE SCO AND ASEAN - I. Abdullin, Adel; I. Sitdikova, Rosa; E. Tyurina, Natalia; D. Iafizova, Liliia (Gênero & Direito, 2019)
This article presents a comprehensive analysis of the institutional forms of regional scientific and technical cooperation in such integration associations as the SCO and ASEAN. The founding documents of the SCO (the Charter of the Shanghai Cooperation Organization) and ASEAN (n the Declaration on the Establishment of ASEAN) define scientific and technical cooperation as one of the tasks of these regional organizations. The authors proceed from the fact that overcoming the obstacles to the development of modern society is unthinkable without reliance on scientific and technological progress, and therefore a joint search for solutions to problems that already exist today and may arise in the 21st century is necessary. The expansion of cooperation in the field of science and technology within the framework of the SCO has been defined as one of the areas of cooperation and an institutional mechanism for the interaction of member states has been created, in which a permanent working group on scientific and technical cooperation holds an important place. One of the significant results in creating the material base for joint research is the SCO University (SCOU). Its main goal is to give a new impetus to the expansion of multilateral educational, scientific and cultural cooperation. The article notes that ASEAN's scientific and technical research is not limited to internal projects. A significant role in the development of this area is played by documents and institutions in which Russia is involved